Slobodan Milošević against the doctrine of „weak Serbia - strong Yugoslavia“ (1986–1992) - Żurek, Piotr (Balcanica Posnaniensia. Acta et studia, 2021)
At the beginning of the 1980s, Serbia became convinced that there was a policy in the SFRY aimed at weakening the country's most numerous nation - the Serbs. Slobodan Milošević gained political capital on his opposition to the doctrine of 'weak Serbia - strong Yugoslavia'. In the face of the collapse of Yugoslavia, the Serbian leader tried to transform the SFRY into a Serb-centric state. At the outbreak of the war, Milošević led to the establishment of the Federal Republic of Yugoslavia. According to the concept of the Serbian president, all Serbian lands were to unite around this country.